A Rationale for development of innovation management business model at mesoeconomic leve - Markova, Olga V. (Opción, 2019)
The goal of this study is to furnish a rationale for networking forms of economic agents' integration as a promising method for improving the management of innovation trends in Russia's economy. Utilizing the method of rank evaluation of normative performance scores, I reveal that the innovation potential of the mesoeconomic system is being put to use ineffectively. In conclusion, a network is the most effective form of object organization in innovation-related systems. For instance, innovation dynamics in horizontal networking links between research institutions and businesses differ dramatically from that occurring in hierarchical or market relations.